Pengetahuan Etnobotani Tumbuhan Obat Pada Penderita Penyakit Lambung di Desa Trusmi Kulon, Kabupaten Cirebon - Mahrani, Aura Sutra; Husain, Fadly (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to understand the ethnobotanical knowledge possessed by the people of Trusmi Kulon Village, especially in the utilization of medicinal plants for people with gastric diseases. This research used a qualitative method with an ethnographic approach. Data collection in this study was carried out through in-depth interview methods, with a question model using semi-structured interview techniques. Interviews were conducted with 13 informants from the general public in Trusmi Kulon Village who were selected based on their knowledge of ethnobotany and history of gastric disease. The researcher also used the PlantNet application to help identify plants. Data analysis used the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results showed that the people of Trusmi Kulon Village have knowledge about the use of medicinal plants that have been passed down from generation to generation. Overall, 34 medicinal plants were found that are believed to be efficacious, but specifically there are 9 medicinal plants used by the community in overcoming gastric diseases. Plant parts used in making medicinal herbs include leaves, flowers, stems, seeds, and rhizomes. The process of processing plants into medicine varies, ranging from boiled, grated, squeezed, burned, pounded, dried and then brewed, rubbed, or eaten directly. Each herb has a different processing method, some are single, some need to be mixed with other ingredients. This finding shows that traditional medicine is still an important part of society as an alternative treatment that is trusted for generations.